2000
DOI: 10.1165/ajrcmb.22.5.3889
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of Granulocyte Macrophage Colony-Stimulating Factor in Human Lung Epithelial Cells by Interleukin (IL)-1 β , IL-4, and IL-13 Involves Both Transcriptional and Post-Transcriptional Mechanisms

Abstract: Interleukin (IL)-1beta stimulates the release of granulocyte macrophage colony-stimulating factor (GM-CSF) from lung epithelial cells. To investigate the molecular mechanisms underlying GM-CSF regulation, we studied GM-CSF production, messenger RNA (mRNA) expression levels, and GM-CSF promoter activity in A549 human alveolar carcinoma cells stimulated with IL-1beta. Coincubation with IL-4 or IL-13 dose-dependently inhibited IL-1beta-induced GM-CSF release. Time-course studies of intracellular and extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 44 publications
(44 reference statements)
2
48
0
Order By: Relevance
“…PKC activation by PMA has been shown to stimulate NF-kB activation and to induce granulocyte-macrophage colonystimulating factor (GM-CSF) expression in A549 cells and human bronchial epithelial cells [40,41]. In addition, several studies have demonstrated airway epithelial cell TNF-a responses to be at least partially sensitive to PKC inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…PKC activation by PMA has been shown to stimulate NF-kB activation and to induce granulocyte-macrophage colonystimulating factor (GM-CSF) expression in A549 cells and human bronchial epithelial cells [40,41]. In addition, several studies have demonstrated airway epithelial cell TNF-a responses to be at least partially sensitive to PKC inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 increases VCAM1 expression on endothelial cells (34), which enhances eosinophil adherence via ␤ 1 integrin. IL-13 also increases CD69 expression on eosinophils (35) and the production of GM-CSF by epithelial cells (36). Both of these actions increase eosinophil survival.…”
Section: Discussionmentioning
confidence: 99%
“…Some inflammatory genes, such as the genes encoding GM-CSF and cyclooxygenase (COX)-2, produce mRNA that is particularly susceptible to the action of ribonucleases, which break down mRNA, thus switching off protein synthesis. Corticosteroids may have inhibitory effects on the proteins that stabilise mRNA, leading to more rapid breakdown and, thus, a reduction in inflammatory protein expression [54][55][56]. Corticosteroids do not appear to have any effect on HuR or tristeraprolin expression, however [57].…”
Section: Nontranscriptional Effectsmentioning
confidence: 99%